Beautification as Systemic Violence: A Critical Anthropological Perspective - Tahsin, Maria (South Asian Journal of Social Sciences and Humanities, 2025)
This study aims to provide a qualitative analysis of the concept of beautification among university female students, analyzing how systemic violence operates through societal structures, institutional norms, and media influences on women’s beautification practices. It also examines the psychological, social, and economic consequences of conformity to beauty norms. Fieldwork was conducted at Comilla University with female students from various departments. Both primary and secondary sources were used for data collection. Respondents were selected using purposive sampling, and a total of 60 participants aged between 20 and 24 years, all currently studying at Comilla University, were interviewed. Qualitative ethnographic approaches guided the research, and data were collected using multiple techniques. Participant observation proved effective, allowing the researcher to live within the community and observe daily life firsthand. The study was further informed by semi-structured interviews, which combined pre-determined questions with the flexibility to explore emerging themes. Research tools included field notes and audio recordings, obtained with the consent of each respondent. Findings reveal that students’ perceptions are conflicted between natural and socially constructed notions of beautification. Beauty norms emerge not from personal preference but as responses to societal expectations, institutional norms, and media influences. As a result of these unattainable beauty standards, students experience social rejection, psychological trauma, and anxiety about unequal job opportunities. This study recommends that policymakers and researchers critically and effectively address SDG-5 in Bangladesh, advocating for a society where women are valued for their intellectual competence and aptitude rather than judged by physical appearance.